Dr. Swati Bhargava : the Nepal earthquake, travel to Ahmedabad - Ravichandran, N. (London : Indian Institute of Management, Ahmedabad, 2017)
The case describes the hardships faced by Dr. Swati Bhargava when she was stranded in Kathmandu, Nepal after an earthquake in April 2015. After the earthquake, the Kathmandu airport was closed and even though Bhargava had a confirmed ticket to Ahmedabad via Delhi from Kathmandu by an Indian Low Cost Airline (ILCA), she could not travel as per the schedule. The ILCA extended only the minimum courtesy to their stranded passengers. Bhargava had to fend for herself in a challenging situation in order to return back to Ahmedabad. While the teaching community in Kathmandu treated Bhargava with care and provided support to facilitate her unexpected extended stay, an organized commercial airline (ILCA) did next to nothing to help the stranded passengers in Kathmandu. As a result Dr. Bhargava considered multiple options as to how the airline could sensitize the system to be responsive and sensitive to such situations should they occur in the future.
Originally published in Ravichandran, N. (2017). Dr. Swati Bhargava: The Nepal Earthquake, Travel to Ahmedabad. QM0277. Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Bhargava, Swati; Nepal Earthquake, 2015 (April 25); Crisis management -- Nepal; International business enterprises -- Management -- Nepal; Corporate culture -- Nepal